Fecundity and egg size in anadromous brown trout Salmo trutta - Rinaldo, Adrian (UiT Norges arktiske universitet, 2020)
Historically, anadromous salmonids provided a necessary provisioning service for Norwegian coastal settlements that has transitioned into the socio-cultural service that they provide today. Over the past decades, human impact has caused anadromous salmonid populations to decline. A recent assessment found many Norwegian sea trout populations to be in poor condition. Reference point management has been used to conserve and manage Atlantic salmon populations, and a similar approach is achievable for the sea trout. This requires data on reproductive traits such as fecundity and egg size due to their importance in establishing population forecasting models. The primary driver of fecundity and egg size is body size. Hitherto, knowledge on fecundity and egg size and their relationship to body size in sea trout is limited due to the body size ranges investigated. The aim of this thesis was to quantify reproductive traits and their relationships to body mass and reproductive allocation in sea trout over a wide range of body sizes and a large geographical area. Two groups of wild sea trout (n = 14 + 18 = 32), and one hatchery-reared population of sea trout (n = 25) was investigated using basic quantitative methods (e.g., weighing, measuring and counting) in combination with imaging techniques. Gonad mass increased linearly with body mass for wild sea trout, and sublinearly with body mass for hatchery-reared sea trout. Absolute fecundity and egg size increased sublinearly with body mass. Relative fecundity decreased with body mass in sea trout. Egg size was smaller in hatchery-reared sea trout than in wild sea trout. Gonadosomatic index was independent of body size for the wild and hatchery-reared sea trout. The results indicated a trade-off between relative fecundity and egg size. Egg size decreased with gonadosomatic index in hatchery-reared sea trout. Within-clutch variation in egg size increased with body mass. In conclusion, this thesis supports and adds to, previous studies on reproductive traits and their ...